Vitamin E effect on osmotic fragility in Î² thalassemia major - Agus Fitrianto; Moedrik Tamam; Nyoman Suci Widyastiti (Paediatrica Indonesiana, 2014)
Background Blood transfusion remains the main therapy for anemia in Î² thalassemia major patients. However, frequent transfusions can cause oxidative stress in response to iron overload. Vitamin E is considered to be the best lipid-soluble exogenous antioxidant in humans. It can protect phospholipid membrane from peroxidarion. Erythrocyte osmotic fragility is a useful test to assess for the improvement of red blood cells in thalassemia patients after vitamin E supplementation.Objective To investigate the effect of vitamin E for improving erythrocyte osmotic fragility in Î² thalassemia major and for decreasing the need for frequent transfusions.Methods T his was a double blind placebo controlled randomized clinical trial on children aged 2-14 years with thalassemia major who received frequent blood transfusions. Fifty subjects were divided into 2 groups: group I with vitamin E supplementation and group II with placebo, as a control group, for a period of 1 month. Pre- and post-treatment data on erythrocyte osmotic fragility and hemoglobin level were analyzed with non-paired T-test.Results Improved erythrocyte osmotic fragility was found: in group I, pre-treatment 31.59 (SD 6.342)% to post-treatment 38.08 (SD 7.165)%, compared to the control group pre-treatment 34.40 (SD 6.985)% to post-treatment 29.26 (SD 9.011)% (P=0.0001). Comparison of the mean delta Hb level in group Â I was 0.94 (SD 0.605) gr% and that of group II was - 0.23 (SD 1.199) gr% (P=0.0001).Conclusion Vitamin E supplementation improves erythrocyte fragility and Hb level in Î² thalassemia major pediatric patients.